(untitled) (Bangladesh Critical Care Journal, 2015)
Objective : To compare the outcome of critically ill patients developing early onset Ventilator-associated pneumonia (VAP) occurring within 96 h of ICU admission and late onset VAP occurring after 96 h of ICU admission in critically ill patients admitted in the ICU of BIRDEM General Hospital of Bangladesh. Study Design: Prospective cohort study. Material and Methods: Study data obtained over a period of 24 months (July 2012 - June 2014) in the ICU of a tertiary care hospital was prospectively analyzed. Subjects were classified by ventilator status: early onset VAP (< 96 hrs of mechanical ventilation) or late-onset VAP (?96 hrs of mechanical ventilation). Baseline demographics and bacterial etiology were analyzed according to the spectrum of status of VAP. Results: The incidence of VAP was 35.73 per 1,000 ventilator days. In our study 52% of the cases were early-onset VAP, while 48% were late-onset VAP. Acinetobacter was the commonest organism isolated from late-onset VAP (p = 0.029) while Pseudomonas was the commonest isolates obtained from early-onset VAP (p = 0.046). Klebsiella, MRSA and E. coli were almost identically distributed between groups (p > 0.05). There is significant difference of sensitivity pattern of Acinetobacter baumannii and pseudomonas aeruginosa in both early and late-onset VAP (p=0.01). The overall mortality rate in our study was 44%. The mortality was significantly higher in the late-onset VAP (62.5%) than that in the early-onset VAP (26.9%) (p=0.011). Conclusion: From this study we conclude that late-onset VAP had poor prognosis in terms of mortality as compared to the early-onset type. The higher mortality in the late-onset VAP could be attributed to older age, higher co-morbidities like diabetes mellitus, COPD and CKD. The findings are similar to findings of other international studies Bangladesh Crit Care J March 2015; 3 (1): 9-13